Internal Brand Management and Its Effects on Employees’ Attitude in an Indonesian Airline Company - Muhammad Irfan Syaebani; Siti Rahmah Muthia; Dindha Vitri Primadini (Program Studi Magister Manajemen FE Unsri, 2021)
ABSTRACTResearch Aims – This study investigates the impact of Internal Brand Management (IBM) towards brand commitment, employee job satisfaction, and intention to stay in an airline company in Indonesia.Design/methodology/approach – This study is a quantitative study and the hypotheses are tested from 131 questionnaires from the employees of an airline company and are analysed using Structural Equation Modelling (SEM).Research Result – The result shows that IBM affects positively brand commitment and employee job satisfaction. Job satisfaction impacts positively brand commitment, while both job satisfaction and brand commitment give a positive effect on the intention to stay.Research limitations – The information and research on IBM are limited especially the implementation of IBM in Indonesia. The literature on IBM is also dominated from a marketing point of view rather than human resource management and strategic management point of view.Originality/Value – This study is conducted in an airline company in Indonesia while the previous researches were conducted in financial institutions in South Africa and Saudi Arabia. Even though IBM comes originally from the marketing concept, but it has a significant impact on determining the attitude and behaviour of employees at work.Keywords : Airline, Brand Commitment, Human Resource, Internal Brand Management, Intention To Stay, Job Satisfaction.